The Relationship Between Knowledge and Perceptions of the Disease and Medication Adherence Among Elderly Patients with PRB Hypertension in the Service Area of the Cimalaka Community Health Center - Mutiara Sari Nur Hasanah; Diding Kelana Setiadi; Sri Wulan Lindasari (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Hypertension is a common chronic non-infectious disease, or noncommunicable disease (NCD), among the elderly and is often referred to as a “silent killer” because its symptoms are rarely apparent. Although the Referral-Back Program (PRB) is available, adherence to antihypertensive medication among the elderly remains a challenge. This study aims to analyze the relationship between knowledge and disease perception and medication adherence among elderly hypertensive patients in the Referral Back Program within the Cimalaka Community Health Center (Puskesmas) service area. Method: This study employed a quantitative correlational method with a cross-sectional design, involving 46 respondents selected through accidental sampling. Data collection in this study was conducted using the Hypertension Knowledge-Level Scale (HK-LS) questionnaire to assess knowledge levels, the Brief Illness Perception Questionnaire (B-IPQ) to evaluate illness perception, and the Morisky Medication Adherence Scale (MMAS-8) to assess medication adherence. Subsequently, the data were analyzed using the Spearman’s rho correlation test to determine the relationship between variables Result: The results of the Spearman’s rho test showed no significant association between knowledge and medication adherence (r = 0.176; p = 0.241) or between illness perception and medication adherence (r = 0.259; p = 0.082). Conclusion: It can be concluded that no significant association was found between knowledge levels and perceptions of the disease and medication adherence among elderly patients with hypertension participating in the Referral-Back Program in the service area of the Cimalaka Community Health Center.